Comparative Efficacy of 2 L Polyethylene Glycol Alone or With Ascorbic Acid vs. 4 L Polyethylene Glycol for Colonoscopy: A Systematic Review and Network Meta-Analysis of 12 Randomized Controlled Trials - Tian, Xu; Shi, Bing; Chen, Hui; Liu, Xiao-Ling; Tang, Rong-Ying; Pi, Yuan-Ping; Chen, Wei-Qing (Frontiers in Medicine, 2019)
Background: Colonoscopy remains an optimal approach for early detection and treatment of gastrointestinal lesions, however adequate bowel preparation is the critical contributor to effective and safe colonoscopy. Polyethylene glycol (PEG)-based bowel cleansing regime has been the first recommendation before colonoscopy, however it remains unknown which regime is the optimal option. Aim: The aim of our study is to determine the comparative efficacy of 2 L PEG alone or plus ascorbic acid (Asc) vs. 4 L PEG alone for bowel cleansing prior to colonoscopy. Methods: We assigned two independent investigators to search and screen potential records, extract essential information, and appraise the risk of bias of individual study accordingly. Then, we adopted RevMan 5.3, Stata 14.0, and WinBUGS 1.4 software to perform all statistical analyses. We also calculated the surface under the cumulative ranking curve (SCURA) in order to rank all regimes. Results: Twelve studies involving 4,106 patients were analyzed finally. Pooled results indicated an improved bowel preparation efficacy in 2 L PEG plus ascorbic acid with split-dose regime rather than in 2 L PEG plus ascorbic acid (OR, 0.25; 95% CI, 0.18–0.36), 4 L PEG with split dose (OR, 3.18; 95% CI, 2.17–4.66), and 4 L PEG (OR, 4.53; 95% CI, 3.07–6.67) regimes, which was confirmed by network meta-analyses; a better compliance in 2 L PEG plus Asc with split dose (OR, 3.08; 95% CI, 1.51–6.30) and 4 L PEG with split dose (OR, 0.43; 95% CI, 0.22–0.82) regime rather than in 4 L PEG regime, but network meta-analyses generated inconsistency results; a higher preference in 2 L PEG plus Asc with split dose regime rather than in 4 L PEG split dose (OR, 2.24; 95% CI, 1.02–4.90), which were not supported by network meta-analyses; no statistically significant difference when all regimes compared with each other in terms of adverse events. Conclusions: As for bowel preparation before colonoscopy, 2 L PEG ascorbic acid with split dose should be optimally prescribed. Further studies investigating the comparative efficacy of 2 L PEG related to 4 L PEG, 4 L PEG with split dose, and 2 L PEG plus ascorbic acid with split dose, respectively are needed.